742 Prioritisation exercise for the probe project (hazardous chemical products register for occupational use in belgium). (24th April 2018) - Ronsmans, Steven; Pauwels, Sara; Temmerman, Anne-Marie; Schryver, Antoon De; Rusu, Dorina; Braeckman, Lutgart; Godderis, Lode
Abstract : Introduction: The PROBE (Hazardous chemical Products Register for Occupational use in Belgium) study consists of a systematic collection of occupational chemical exposure data of Belgian workers. To test the feasibility of our approach a pilot study will be conducted using a concise list of priority chemicals. Methods: A targeted method was used to construct a priority list of chemicals relevant for the Belgian workplace context. In a first step, five recent European reports on prioritisation exercises of workplace chemicals were reviewed. All reports constructed a priority list based on different combinations of relevant sources: hazard information, health effects, exposure data, volume used and limit value databases. The appearance of a chemical in at least 2 prioritisation reports was used as a selection criterion for our list. In this way, we used the accumulated expertise of these reports to extract a preliminary list of 16 chemicals. In a second step relevancy for the Belgian workplace context was evaluated using a number of sources: data on occupational exposure collected by Occupational Health Services, available biomonitoring and workplace measurements, REACH registrations for Belgium, data from the labour inspection and data on recognised occupational diseases by the Belgian Fund for Occupational Diseases. Fourteen out of the 16 chemicals listed in the preliminary list appeared to be relevant for the Belgian context. Result: A priority list of 14 chemicals was constructed for the pilot study of PROBE: crystalline silica, diesel exhaust and PAHs, wood dust, formaldehyde, asbestos, isocyanates, benzene, organic solvents, lead, beryllium, powder coating, refractory ceramic fibres, welding fumes and cadmium. Discussion: This stepwise approach made it feasible to select a concise number of priority chemicals. In the coming months, exposure data on these chemicals will be collected in a sentinel study and an evaluation of the appropriateness of the selection will be performed.